KOMBINASI PERCEPTUAL MOTOR PROGRAM DAN NEURODEVELOPMENTAL TREATMENT LEBIH BAIK DARIPADA KOMBINASI KINESIOTAPING DAN NEURODEVELOPMENTAL TREATMENT DALAM MENINGKATKAN KEMAMPUAN DUDUK PENDERITA CEREBRAL PALSY - Triandari, Listya; Tirtayasa, Ketut; Irfan, Muhammad; Wihandani, Desak Made; Satriyasa, Bagus Komang; -, Sugijanto (Sport and Fitness Journal; Volume 6, No.2, Mei 2018, 2018)
One of the deviation on brain growth was cerebral palsy (CP). The problem in cerebral palsy patient was inability to sitting. The aim of this study is to prove that additional of perceptual motor program is better than kinesiotaping in neurodevelopmental treatment in improving ability sitting in cerebral palsy patients. The method of study was pre and post test design. Fourteen cerebral palsy children with quadriplegi type that unable to sit as the sample in this study. The samples divided into two group that was group I (perceptual motor program and neurodevelopmental treatment) and group II (kinesiotaping and neurodevelopmental treatment). The intervention was applied in 60’ per session, twice session per week for 12 weeks. The score of measurement was measured by Level of Sitting Scale (LSS). The result of research showed (1) improvement of the LSS score in the group I as pre test 1.86 ± 0.69 and post test 4.00 ± 0.82, (2) improvement of the LSS score in the group II as pre test 2.00 ± 0.82 and post test 2.86 ± 1.07, (3) there was significance difference of the LSS score between group I and II with p = 0.029 (p < 0,05). It was concluded that the combination of perceptual motor program and neurodevelopmental treatment was better than the combination of kinesiotaping and neurodevelopmental treatment in increase sitting ability in cerebral palsy patients.